2016
DOI: 10.2135/cropsci2015.11.0665
|View full text |Cite
|
Sign up to set email alerts
|

Maize Stalk Lodging: Flexural Stiffness Predicts Strength

Abstract: Late‐season stalk lodging in maize (Zea mays L.) is a major agronomic problem that has far‐reaching economic ramifications. More rapid advances in lodging resistance could be achieved through development of selective breeding tools that are not confounded by environmental factors. It was hypothesized that measurements of stalk flexural stiffness (a mechanical measurement inspired by engineering beam theory) would be a stronger predictor of stalk strength than current technologies. Stalk flexural stiffness, rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 10 publications
6
89
0
Order By: Relevance
“…Second, data from DARLING was analyzed to check that it was in agreement with laboratory based protocols for testing maize stalks in bending. In particular, laboratory experiments have demonstrated that stalk flexural stiffness is strongly correlated with stalk bending strength (Robertson et al, 2016). This same correlation is observed in the data collected using DARLING (see Figure 7).…”
Section: Validation and Accuracy Of Measurementssupporting
confidence: 72%
“…Second, data from DARLING was analyzed to check that it was in agreement with laboratory based protocols for testing maize stalks in bending. In particular, laboratory experiments have demonstrated that stalk flexural stiffness is strongly correlated with stalk bending strength (Robertson et al, 2016). This same correlation is observed in the data collected using DARLING (see Figure 7).…”
Section: Validation and Accuracy Of Measurementssupporting
confidence: 72%
“…The mechanical stability of plants depends on the material properties of tissues and the geometry, shape, and size of plant organs, as well as the genetics, environment, and loading forces applied to plants (Berry & Berry, 2015; Niklas, 1992; Paolillo & Niklas, 1996). Therefore, breeding for superior stem mechanical traits can enhance resistance to wind‐induced lodging in a variety of crops (Berry & Berry, 2015; Li et al., 2009; Robertson, Lee, Julias, & Cook, 2016; Sposaro, Berry, Sterling, Hall, & Chimenti, 2010). Although the mechanical properties of stems from different crops have been reported, only a few of these studies have included genetic analysis of stem mechanical traits.…”
Section: Introductionmentioning
confidence: 99%
“…Root lodging can cause a varying degree of yield losses (Bian et al, 2016). Stalk lodging, which involves breakage of a stalk below the ear, is usually observed as plants approach physiological maturity (Robertson et al, 2016) and often leads to total loss of the grain (Albrecht et al, 1986). Improving stalk lodging resistance (see Box 1 for description) offers an opportunity to substantially increase maize production without increasing agricultural inputs including irrigation, fertilizer, and crop management expenses.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of stalk lodging resistance has traditionally relied on late-season stalk lodging incidence counts obtained by recording the number of lodged plants in a defined area. Currently, lodging counts are the most widely used method for determining lodging resistance in breeding programs (Robertson et al, 2016). However, this method is confounded by numerous factors including varying levels of disease, pest pressure, soil fertility, wind velocity, and other weather and environmental conditions at the locations used for evaluation (Thompson, 1972;Hondroyianni et al, 2000;Flint-Garcia et al, 2003a;Hu et al, 2012;Robertson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%